Development of an e-LKPD Based on Problem-Based Learning Using Liveworksheets for IPAS Learning in Fourth Grade Elementary School - Radhiatun Mardhiah; Yeni Erita; Nur Fadillah (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
This research is motivated by the limited use of digital-based student worksheets (E-LKPD) in elementary schools, particularly in social science learning. The purpose of this study is to develop a E-LKPD based on Problem-Based Learning using Liveworksheets for social science learning in Grade IV of elementary school, focusing on cultural diversity and local wisdom. This research adopts a Research and Development (R&D) approach using the ADDIE development model.The results showed that the E-LKPD achieved a material validity score of 92%, language validity of 88%, and media validity of 94%, with an average of 91.3%, categorized as very valid. Practicality was assessed through questionnaires administered to teachers and students. At UPTD SD Negeri 11 Guguak VIII Koto, the practicality scores were 94% for teachers and 95.1% for students. At UPTD SD Negeri 05 Tujuah Koto Talago, the results were 94% for teachers and 95.6% for students, while at UPTD SD Negeri 01 Guguak VIII Koto, the results were 96% for teachers and 95.8% for students. The effectiveness test using N-Gain analysis showed results of 81.01% at UPTD SD Negeri 11 Guguak VIII Koto, 81.03% at UPTD SD Negeri 05 Tujuah Koto Talago, and 83.33% at UPTD SD Negeri 01 Guguak VIII Koto each falling into the effective category. It can be concluded that the E-LKPD based on Problem-Based Learning using Liveworksheets for Grade IV on social science learning in elementary schools is valid, practical, and effective.